Birds of a feather: homophily and sexual network structure in sub-Saharan Africa. (March 2013) - Kenyon, C; Colebunders, R
Sexual partner homophily is the tendency of individuals to choose partners similar to themselves. The extent and nature of partner homophily influences the structure of sexual networks and hence the spread of sexually transmitted infections (STIs). In this paper, we compare homophily by ethnicity, age and educational status in representative populations from five African cities in Benin (Cotonou), Cameroon (Yaounde), Kenya (Kisumu), Zambia (Ndola) and South Africa (Carletonville). We find low rates of homophily by age and high rates for educational status throughout the region. There is a large variation in homophily by ethnicity between these five cities, with rates lowest in Ndola. In Carletonville, there is a gendered difference in homophily by ethnicity. We discuss the possible implications these variations in the extent and type of homophily may have for STI transmission in the region.